187 Optimal standardized ileal digestible lysine and methionine + cysteine to lysine ratio for 30. (7th December 2018) - Htoo, J; Ho, T; Dao, T; Carpena, M; Le, N; Vu, C; Nguyen, Q
Abstract: Two experiments were conducted using crossbred growing pigs. In Exp. 1, 72 pigs (initial BW 28.9 ± 0.27 kg) were assigned to 6 diets adequate in all AA but with increasing Lys content [0.70, 0.80, 0.90, 1.00, 1.10 and 1.20% standardized ileal digestible (SID) Lys] with 6 pen replicates (2 pigs) per treatment for 28 days to determine the SID Lys requirement. In Exp. 2, 72 pigs (initial BW 32.9 ± 0.41 kg) were assigned to 6 dietary treatments adequate in all AA except for Met+Cys and Lys (50, 55, 60, 65, 70, and 64% SID Met+Cys:Lys ratios) with 6 pen replicates (2 pigs/replicate) per treatment for 21 days to determine the optimal SID Met+Cys:Lys ratio. Diets 1 to 5 were formulated to contain 1.0% SID Lys to be second limiting and diet 6 contained 1.11% SID Lys. In both experiments, diets were formulated based on corn, rice bran and soybean meal using analyzed ingredients AA contents. Data were analyzed by ANOVA using the GLM procedure of SAS with initial BW and diets included in the model. In Exp. 1, increasing Lys increased the overall ADG and G:F linearly (P < 0.001) and decreased plasma urea nitrogen (PUN; d 29) concentration quadratically (P =0.001). The curvilinear plateau and linear broken-line models estimated the SID Lys to be 1.36, 1.38 and 1.28% for ADG, G:F and PUN, respectively. In Exp. 2, increasing SID SAA:Lys ratio increased (P < 0.001) ADG and G:F and decreased PUN. The curvilinear plateau and the broken-line models estimated the optimum SID Met+Cys:Lys ratio to be 65.5 and 63.0% for ADG, and 66.7 and 64.0% for G:F, respectively. On average, optimal SID SAA:Lys ratio for 30–50 kg growing pigs was 65.2%. The SID Lys requirement and SID SAA:Lys ratio required for growing pigs are slightly higher than some recommendations.